2017
DOI: 10.1002/jpen.1023
|View full text |Cite
|
Sign up to set email alerts
|

Direct Percutaneous Endoscopic Jejunostomy: Procedural and Nutrition Outcomes in a Large Patient Cohort

Abstract: DPEJ is a successful and safe procedure that effectively provides access for EN support in malnourished patients and patients with postoperative UGI cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
(35 reference statements)
4
16
0
Order By: Relevance
“…The 1-year survival rate was reported to be around 50%. 19,22 We demonstrate that the mortality after DPEJ was 34.3% at 1 year and 51.4% at 2 years, and the survival curve for DPEJ patients was similar to that of PEG patients in our study with similar demographic data. However, the survival curve of the DPEJ group dropped more than that of the PEG group after 2 years of placement.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The 1-year survival rate was reported to be around 50%. 19,22 We demonstrate that the mortality after DPEJ was 34.3% at 1 year and 51.4% at 2 years, and the survival curve for DPEJ patients was similar to that of PEG patients in our study with similar demographic data. However, the survival curve of the DPEJ group dropped more than that of the PEG group after 2 years of placement.…”
Section: Discussionsupporting
confidence: 77%
“…Previously reported severe AEs of DPEJ included bleeding, bowel or gastric perforation, ileus, volvulus, abscess, sepsis, and aspiration, with frequency ranging from 1.1% to 7.7%. 9,11,13,14,17,19 In these AEs, bowel perforation, ileus, and volvulus are characteristic of DPEJ but not PEG. Although PEG is placed in the epigastrium region in most cases, an appropriate DPEJ site depends on each patient in view of his/her entire abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Though similar to PEG placement, D-PEJ is a considerably more challenging technique. In the two largest retrospective cohorts on D-PEJ outcome involving a total of 738 patients, successful placement was achieved in 68 % -83 % [35,38]; this may be higher if a double-balloon or single-balloon enteroscope is used [39].…”
Section: Percutaneous Endoscopic Gastrostomy With Jejunal Extension (mentioning
confidence: 97%
“…Moreover, a prospective comparative study suggested that early feeding after PEG tube insertion could also help reduce inpatient stay [84]. Finally, in the two largest series of D-PEJ, the initiation of enteral feeding was reported to be within 4 to 24 hours after placement [35,38]. [85,86,90,91], respectively.…”
Section: Using the Percutaneous Enteral Tube (Peg Peg-j D-pej) For mentioning
confidence: 99%
See 1 more Smart Citation